An alternative approach for supportive supervision and skill measurements of health workers for integrated management of neonatal and childhood illnesses program in 10 districts of Haryana - Arun K Aggarwal; Rakesh Gupta; Dhritiman Das; Anar S Dhakar; Gourav Sharma; Himani Anand; Kamalpreet Kaur; Kiran Sheoran; Suresh Dalpath; Jaidev Khatri; Madhu Gupta (Wolters Kluwer Medknow Publications, 2018)
Context: "Integrated Management of Neonatal and Childhood Illnesses" (IMNCI) needs regular supportive supervision (SS). Aims: The aim of this study was to find suitable SS model for implementing IMNCI. Settings and Design: This was a prospective interventional study in 10 high-focus districts of Haryana. Subjects and Methods: Two methods of SS were used: (a) visit to subcenters and home visits (model 1) and (b) organization of IMNCI clinics/camps at primary health center (PHC) and community health center (CHC) (model 2). Skill scores were measured at different time points. Routine IMNCI data from study block and randomly selected control block of each district were retrieved for 4 months before and after the training and supervision. Statistical Analysis Used: Change in percentage mean skill score difference and percentage difference in median number of children were assessed in two areas. Results: Mean skill scores increased significantly from 2.1 (pretest) to 7.0 (posttest 1). Supportive supervisory visits sustained and improved skill scores. While model 2 of SS could positively involve health system officials, model 1 was not well received. Outcome indicator in terms of number of children assessed showed a significant improvement in intervention areas. Conclusions: SS in IMNCI clinics/camps at PHC/CHC level and innovative skill scoring method is a promising approach.